2009
DOI: 10.4251/wjgo.v1.i1.69
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between colorectal low- and high-grade mucinous adenocarcinoma with MUC1 and MUC5AC

Abstract: AIM:To explore useful prognostic factors for mucinous adenocarcinoma (MAC) in the colon and rectum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…44 Similarly, MUC6 expression in colorectal tumors has been restricted largely to adenomas and serrated polyps, the latter have been found to express MUC6 commonly, 30,49 whereas several groups have reported MUC6 expression in cancers as rare or absent, 16,50,51 even in mucinous carcinomas. 52 In 1999, Toyota et al 53 described the existence of the CIMP in colorectal carcinoma, in which hypermethylation is induced in a wide variety of genes. Ferracin et al 9 found that CIMP-positive colorectal cancers were more likely than CIMPnegative cancers to show areas of mucinous differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…44 Similarly, MUC6 expression in colorectal tumors has been restricted largely to adenomas and serrated polyps, the latter have been found to express MUC6 commonly, 30,49 whereas several groups have reported MUC6 expression in cancers as rare or absent, 16,50,51 even in mucinous carcinomas. 52 In 1999, Toyota et al 53 described the existence of the CIMP in colorectal carcinoma, in which hypermethylation is induced in a wide variety of genes. Ferracin et al 9 found that CIMP-positive colorectal cancers were more likely than CIMPnegative cancers to show areas of mucinous differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Mucinous components were divided into two groups by the quality of mucin (low or high grade) (20). The Q score for mucinous components was calculated by multiplying the quality of mucin by the proportion of the area.…”
Section: Kras Mutation Analysismentioning
confidence: 99%
“…Studies have shown that during adenoma-adenocarcinoma progression, the expression of MUC5AC is upregulated[ 41 ], which may be associated with transcription factors such as Smad-4, SP-1[ 45 ], GATA-6 and HNF-4α[ 46 ], sex determining region Y-box 2[ 47 ], and trefoil factor 3[ 48 ]. Although MUC5AC expression is upregulated in MAC, the expression of MUC5AC in low-grade MAC is significantly higher than that of high-grade MAC[ 4 ]. At the same time, the lack of MUC5AC expression is an indication of more aggressive colorectal tumors, as patients with negative MUC5AC expression have a poorer prognosis than those with positive expression[ 49 ].…”
Section: Molecular Characteristics Of Colorectal Macmentioning
confidence: 99%
“…Compared to non-MAC (NMAC), the clinicopathological characteristics, molecular features, response to chemo-/radiotherapy, and prognosis of MAC are evidently different. MAC are divided into two types based on the degree of histological structural differences: One type is the low-grade MAC, which originates from well-differentiated to moderately differentiated adenocarcinoma and papillary carcinoma, whereas the other type is the high-grade MAC, originated from poorly differentiated adenocarcinoma and signet ring cell carcinoma (SRCC)[ 4 ]. Currently, the prognosis of MAC remains controversial.…”
Section: Introductionmentioning
confidence: 99%